Answer:
pp
Step-by-step explanation:
pp
<u>Solution </u><u>1</u><u> </u><u>:</u><u>-</u>
Given expression ,
We know that,
Therefore , this can be written as ,
![\implies \sqrt[4]{13^3}](https://tex.z-dn.net/?f=%5Cimplies%20%5Csqrt%5B4%5D%7B13%5E3%7D%20)
<u>Solution</u><u> </u><u>2</u><u>:</u><u>-</u>
Given expression ,
We know that,
Therefore, this can be written as ,
![\implies 24^{\frac{10}{3}}](https://tex.z-dn.net/?f=%5Cimplies%2024%5E%7B%5Cfrac%7B10%7D%7B3%7D%7D)
Answer:
123added 23
Step-by-step explanation: